A Guide to the UNCITRAL Arbitration Rules - Croft, Clyde; Kee, Christopher; Waincymer, Jeff (Cambridge : Cambridge University Press, 2013)
The first version of the UNCITRAL Arbitration Rules was endorsed by the General Assembly of the United Nations in December 1976. Now considered one of UNCITRAL's greatest successes, the rules have had an extraordinary impact on international arbitration as both instruments in their own right and as guides for others. The Iran-US Claims Tribunal, for example, employs a barely modified version of the rules for all claims, and many multilateral and bilateral foreign investment treaties adopt the UNCITRAL Rules as an arbitral procedure. The Rules are so pervasive and the consequences of the new version potentially so significant that they cannot be ignored. This commentary on the Rules brings the official documents together in one volume and includes the insights and experiences of the Working Group that are not included in the official reports.
Title from publisher's bibliographic system (viewed on 03 May 2017).
Keywords: International commercial arbitration; Foreign trade regulation